The Effects of COVID-19 on the Returns and Volatilities of Global Stock Indexes - Fang, Jing (International Journal of Global Economics and Management, 2024)
At the beginning of 2020, COVID-19 broke out around the world, and its impact on the global economy exceeded expectations. Countries declared states of emergency one after another. The outbreak not only triggered a crisis of supply, demand, investment, and supply chain disruptions but also transmitted to the financial sector. Global risk aversion is rising rapidly, and global stock markets continue to plummet, threatening to trigger further financial crises. To investigate the impact of COVID-19 on the financial sector and to prevent and mitigate financial risks, this paper examines the impact of COVID-19 on global stock markets from a global perspective. Firstly, selected data of seven global stock indices using WRDS and S&P Capital IQ databases. After processing these data, ARMA-GARCH modeling was carried out using the data before the outbreak and the data for the whole sample period respectively. Then, the residuals of the model were subjected to L-B and ARCH-LM tests to determine the fit of the model for different stock indices and different periods. Next, determine if the return and volatility of the equity index have changed during COVID-19 based on the goodness of fit. The results of the study show that: (1) The outbreak of COVID-19 has had a serious impact on the yields and volatility of major global equity indices. As can be seen from the descriptive statistics of the data, particularly around March 2020, each of the sample equity indices experienced high volatility. (2) By fitting the post-outbreak data using the pre-outbreak fitted model, it was found that the fit was poor. This suggests that the outbreak of the new crown epidemic had a significant impact on the process of generating stock data. (3) The results of this paper show that the data for the China SSE Composite Index after the outbreak still fit the pre-outbreak fitted model well. This also indicates that the Chinese mainland stock market has shown greater stability than other markets when all major world stock indices were significantly hit by COVID-19.